Bringing a Gene-Activated Bone Substitute Into Clinical Practice: From Bench to Bedside - Bozo, Ilia Y.; Drobyshev, Alexey Y.; Redko, Nikolay A.; Komlev, Vladimir S.; Isaev, Artur A.; Deev, Roman V. (Frontiers in Bioengineering and Biotechnology, 2021)
Bone grafting and reconstruction are still challenging in clinical practice because of the limitations of bone autografts and the drawbacks of currently approved bone substitutes. We thus developed a gene-activated bone substitute based on octacalcium phosphate and naked plasmid DNA carrying the vascular endothelial growth factor gene. This advanced combined therapy medicinal product had no cytotoxic effects in vitro, slightly decreased bone marrow mesenchymal stromal cell (MSC) doubling time, and was characterized by a prolonged level of gene construct delivery in vivo in a luciferase bioimaging assay. In the model of critically sized cranial bone defects in rabbits, the gene-activated matrix increased bone tissue formation through angiogenesis induction. After preclinical studies, we conducted an open-label non-randomized clinical trial (NCT03076138). The primary study outcome was the proportion of patients with newly formed bone tissue within the surgical area as measured by computed tomography within 6 months after surgery. The main secondary outcomes included frequencies of adverse events (AEs) and serious adverse events (SAEs) as well as the surgical failure rate. After completing the clinical trial, the patients had dental implants placed in the bone grafting area, and trephine biopsy samples were collected. In total, 20 patients with alveolar ridge atrophy (n = 16) and jaw bone defects (n = 4) were enrolled in the study. There were no AEs or SAEs during the clinical trial or the follow-up period (30 months). In all patients, newly formed tissues with a bone density of 908.13 ± 114.40 HU were detected within the zone of bone grafting. There were no significant differences between the subgroups of patients with atrophy and bone defects: 915.28±125.85 and 879.56±48.36 HU, respectively (p = 0.60). Histological analysis showed that the bone grafting area comprised newly formed bone tissue with some fragments of the gene-activated bone substitute partially resorbed and integrated with bone, without fibrous tissue in between. The preclinical data and clinical trial results proved the feasibility, safety, and efficacy of the investigated material for jaw bone grafting, allowing us to bring the world’s first gene-activated bone substitute from bench to bedside.